Nonverbal competence in researching the communicative and organizational skills of teachers /Competența nonverbală în cercetarea aptitudinilor comunicative şi organizatorice a cadrelor didactice - BÎTCA Lucia (EcoSoEn: Ştiinţe Economice, Sociale şi Inginereşti = Economics, Social and Engineering Sciences)
Arising from the complexity and multidisciplinarity of the problem of nonverbal communication and impression management in the organizational environment, its investigation constitutes a common subject for several sciences, being located at the confluence of social psychology of personality, communication psychology, educational psychology, organizational psychology and business psychology, reflecting in the same way, the contemporary trend of mutual approximation and escalation of the boundaries of scientific fields.